Intergroup forgiveness: East Timorese and Angolan perspectives - Felix Neto (2007)
The present study is a survey on intergroup forgiveness conducted among people from East Timor and Angola, most of whom have been personally touched by the various conflicts affecting their countries. Only one of the two aspects of intergroup forgiveness was assessed: granting forgiveness. A sample of 354 East Timorese adults was presented with a questionnaire addressing the meaningfulness of intergroup forgiveness and possible conceptions about granting intergroup forgiveness. Using exploratory factor analysis, an eight-factor model was derived from the participants' responses. Using confirmatory factor analysis, this model was subsequently tested on a sample of 250 Angolan adults. In both samples, a large majority of participants agreed with the idea that a group of people can forgive another group of people. Furthermore, the model derived from the East Timorese data also fitted the data from the Angolan sample: in both samples, the participants appeared to have articulated conceptions on what could define an intergroup granting of forgiveness. Specifically, a majority of participants agreed with the idea that (a) the aim of this process is reconciliation and that intergroup forgiveness is not strictly conditional on adequate reparation or compensation, and (b) this process must be democratic; in other words, granting forgiveness should be decided by a majority, and only then could forgiveness be granted on behalf of the whole community.